2021
DOI: 10.3389/fpls.2021.754287
|View full text |Cite
|
Sign up to set email alerts
|

Lentil and Fava Bean With Contrasting Germination Kinetics: A Focus on Digestion of Proteins and Bioactivity of Resistant Peptides

Abstract: Germination offers advantages to improve legume protein digestibility as it disintegrates seed structure and hydrolyzes proteins and anti-nutrients. Seed permeability (related to polyphenol content of seed coats) is an important factor affecting the duration of seed germination and its impact on protein digestibility and bioactivity. The objective was to compare the effect of seed germination on protease activity, structure, and proteolysis of four selected legumes with contrasting seed coat polyphenol profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
4
14
0
Order By: Relevance
“…Germination time caused a more pronounced impact than temperature on the content of this antinutritional compound, which decreased as germination time increased, especially at higher temperatures ( Figure 4 ). In agreement with our results, previous studies have shown reduced phytic acid content in sprouted cereals and legumes [ 18 , 36 , 42 , 52 ]. The results of the present study suggest that activation of endogenous phytases, enzymes that hydrolyze phytic acid to lower inositol phosphates and free phosphorus in sprouted lentils occurs at longer sprouting times, and reductions of 50% in the levels of this compound can be achieved at germination times of 5 days ( Figure 4 ).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Germination time caused a more pronounced impact than temperature on the content of this antinutritional compound, which decreased as germination time increased, especially at higher temperatures ( Figure 4 ). In agreement with our results, previous studies have shown reduced phytic acid content in sprouted cereals and legumes [ 18 , 36 , 42 , 52 ]. The results of the present study suggest that activation of endogenous phytases, enzymes that hydrolyze phytic acid to lower inositol phosphates and free phosphorus in sprouted lentils occurs at longer sprouting times, and reductions of 50% in the levels of this compound can be achieved at germination times of 5 days ( Figure 4 ).…”
Section: Resultssupporting
confidence: 94%
“…The maximum protein value in sprouted lentil flour was predicted at 22 °C and 3 days ( Table 2 ). These results agree with studies performed by other authors where an enhancement in protein levels was observed during lentil germination beyond 3 days at 20–25 °C [ 36 , 37 , 38 ]. The high amino acid biosynthetic activity that takes place during germination and the synthesis of enzymes in sprouting seeds [ 38 , 39 ] may be responsible for the increased protein levels in sprouted lentil flour.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is expected that more methods to accelerate germination can be developed. It was reported that the contents of certain antinutritional factors (e.g., trypsin inhibitor) of certain legumes decreased with the prolongation of the germination process (Bautista‐Expósito et al., 2021). This remains to be verified with adzuki beans.…”
Section: Applications Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…Bautista‐Expósito et al (2021) germinated different cultivars of fava and lentil beans namely: maxim red lentil from UoS (DL), low tannin/low vicine–convicine fava bean (ZF), low tannin (gray zero‐tannin) lentil (GZL), and beluga lentil (BL) and isolated antioxidative bioactive peptides from them. Their derived flours were subsequently digested with the INFOGEST 2.0 protocol of static in vitro simulated gastrointestinal digestion and sequenced peptides whose antioxidant bioactivities were predicted from the BIOPEP‐UWM™ database include: SKPHTIFLPQFT (from GZT), SRNPIYSNKFGK and NPIYSNKFG (from BL), FLPQFTDADF (from DL), LSPGDVLVIPAGYPVAIK, and YNAAWDPSNGK (from ZF).…”
Section: Antidiabetic and Antioxidative Mechanisms Of Sprouted Bioact...mentioning
confidence: 99%